Jesús GIRÓN, Ricardo LÁZARO y Fernando RAMÓN (eds.), “Me amó y se entregó por mí” (Gal 2,20). Libro homenaje a Juan Miguel Díaz Rodelas, Maliaño (Cantabria): Sal Terrae («Presencia Teológica», 313), 2023, X+872 pp., 16 x 23, ISBN 978-84-293-3175-2. (Scripta Theologica, 2025)
Book Review